Zeolite A-Carbon Membranes: Possibilities in H2 Purification and how to Overcome their Shortcomings - Varela-Gandía, Francisco J.; Lozano-Castelló, Dolores; Cazorla-Amorós, Diego; Berenguer-Murcia, Ángel (Journal of Membrane and Separation Technology, 2017)
This work describes the modification of zeolite Na-LTA membranes supported on macroporous carbon materials, prepared by a combination of secondary hydrothermal treatment followed by different alternative post-synthesis procedures, which aim at improving the permeance properties of the as-synthesized Na-LTA membranes with a simulated reformer mixture (H2, CO, CO2 and H2O) towards their use in a hydrogen purification device.These post-synthetic treatments include the deposition of a thin layer of amorphous silica formed by the hydrolysis of a silicon alcoxide, the coating with a thin metallic film by electroless plating, and the deposition of noble metal nanoparticles. Our results indicate that some of these treatments, which may be performed very quickly compared to other treatments which are generally used in order to improve the quality of the membranes, result in membranes which may effectively separate H2 from CO under simulated reformer conditions. Considering the simple approach employed in some of the cases described in this study, the potential benefits should be considered highly interesting in fields such as membrane recovery and membrane selectivity control.